Probabilities of Default and the Market Price of Risk in a Distressed Economy - Segoviano, Miguel (IMF Working Papers; Working Paper, 2011)
We propose an original method to estimate the market price of risk under stress, which is needed to correct for risk aversion the CDS-implied probabilities of distress. The method is based, for simplicity, on a one-factor asset pricing model. The market price of risk under stress (the expectation of the market price of risk, conditional on it exceeding a certain threshold) is computed from the price of risk (which is the variance of the market price of risk) and the discount factor (which is the inverse of the expected market price of risk). The threshold is endogenously determined so that the probability of the price of risk exceeding it is also the probability of distress of the asset. The price of risk can be estimated via different methods, for instance derived from the VIX or from the factors in a Fama-MacBeth regression.